Renal Colic: A Red Herring for Mucocele of the Appendiceal Stump - Sameera Ganti (Case Reports in Emergency Medicine, 2018)
Flank pain with hematuria is a common presentation in the emergency department. The commonest differential diagnosis of these patients is renal/ureteric calculus or pyelonephritis. These patients are usually treated with analgesia, antibiotics in case of pyelonephritis, and are discharged with an outpatient referral to a urologist. This case report describes a 51 year old male who presented to the ED for recurrent flank pain and hematuria. Bedside ultrasonography in the ED demonstrated a cystic lesion in the renal area. CT urography revealed an appendiceal stump mucocele and patient was transferred under surgical care. This case highlights the importance of the utility of bedside ultrasound in patients presenting to the ED with flank pain or abdominal pain which can lead to expedited assessment and appropriate management.